The effects of plant structure and flow properties on the physical response of coastal dune plants to wind and wave run-up. (31st October 2021) - Innocenti, Rachel A.; Feagin, Rusty A.; Charbonneau, Bianca R.; Figlus, Jens; Lomonaco, Pedro; Wengrove, Meagan; Puleo, Jack; Huff, Thomas P.; Rafati, Yashar; Hsu, Tian-Jian; Moragues, Maria V.; Tsai, Benjamin; et al.
Abstract: Vegetation is an important feature of coastal dunes and is often managed to stabilize restored dunes and provide coastal protection. Despite a high investment in planting and management efforts, little is known about how vegetation is affected by wind and wave run-up. The objectives of this study were to 1) investigate the lift forces and drag moments experienced by coastal dune vegetation from wind and wave run-up and 2) relate them to flow properties and plant morphology. Panicum amarum, Ammophila breviligulata, A. arenaria and Cakile maritima were subjected to laboratory wind and wave run-up conditions. Measurements were taken of fluid velocity, run-up depth, Reynolds number, and plant biophysical properties. The plant lift and drag responses were recorded with the use of a novel sensor designed to address the complexities induced by the flexibility and morphology of real vegetation under varying conditions. Regression analysis was used to describe the relationships between plant response and plant structure and flow properties. Experiments showed that wind induced a constant lift force and drag moment on plants over time, whereas run-up induced plant response was time-dependent. Plant height (R 2 = 0.64, p < 0.001) and number of leaves (R 2 = 0.67, p = 0.30) were the most important predictors of drag moment from wind and run-up experiments, respectively. Plant drag coefficients from wind (5.0 × 10 −4 to 3.6 × 10 −2 ) and run-up (2.7 × 10 −3 to 1.7) were negatively correlated with flow turbulence, indicating that coastal dune plants likely have biophysical adaptations to the induced forces, such as a propensity for streamlining. In particular, our data suggests that tall and thin dune grasses are best adapted and used on the dune crest and fronts to mitigate wind energy, while low shrubby plants are best used on the backbeach or dune toe to reduce run-up energy. Our study provides valuable information on the ability of dune vegetation to interrupt flow, such that modelers and managers can better understand how to best protect coastlines. Highlights: A uniquely designed force sensor was used to detect plant physical response to wind and run-up. We compared drag moments to focus on the rotation about the axis where the stem meets the ground. Plants had a steady physical response to wind, and a time-dependent response to run-up events. Plant height and number of leaves predicted drag moment from wind and run-up, respectively.